Can store image moderate the influence of religiosity level on shopping orientation and customers' behavior in Indonesia?. Issue 1 (23rd December 2020) - Ratnasari, Ririn Tri; Ula, Ulfa Fadilatul; Sukmana, Raditya
Abstract : Purpose: This study aims to investigate the effects of religiosity level on the shopping orientation and behavior of Muslim customers and how to store image moderates this relationship. Design/methodology/approach: This study uses a positive approach and partial least square analysis technique on samples of Muslim customers in major cities in Indonesia, who have purchased products in the Syariah supermarket such as Sakinah Supermarket and 212 supermarkets at least twice within the past three months. The sampling method used in this study is convenience sampling, with a total of 117 respondents. Findings: The results reveal that religiosity level significantly affects the Muslim customers' shopping orientation subsequently impacts consumer shopping behavior. The result is in line with the rising trend by a society that begins to define successful businesses that touch upon the spiritual aspects of the shoppers. Customers with higher religiosity prefer higher quality products and customers who have lesser levels of religiosity establish different shopping characteristics and behavior. This eventually forms an orientation in shopping behavior. Furthermore, it is found that the store image significantly strengthens the influence of the impact of shopping orientations on Muslim customers' behavior. Practical implications: Marketers can increase the image of Islamic stores by implementing the principle of a smile, greeting, address to every customer who shops, managing the cashier queue to prevent ikhtilath (meeting between men and women) and adding decorations and calligraphy ornaments. Marketers can create membership cards, posters or billboards about the products that are being discounted or promoted to increase customer numbers image enhancement. Originality/value: This study used specific variables that represent religiosity in the retail sector. It offers an analysis of how Muslim customers' religiosity can affect their shopping orientation and behavior. The study is conducted in Indonesia, where research on this topic is still limited.